EFL Learners Attitude toward English Phonetics Learning in English Program at IAIN Parepare - Dian Aisyah Abidin; Ambo Dalle; Abdul Haris Sunubi; Zulfah Fakhruddin; Magdahalena Tjalla (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Learners Attitude referred to the mindset, beliefs, opinions, and emotional disposition that learners bring to the learning process. Attitude plays a crucial role in shaping learners' engagement, motivation, and success in acquiring new knowledge and skills. The research aimed to identify of the attitudes of EFL learners in English program at IAIN Parepare toward their English phonetics learning. This research used quantitative design with data collection technique used questionnaire form with followed likert scale and sample of the research were 70 students from semester 3th and 5th of English Education Department of IAIN Parepare using simple random sampling. Analysis data used descriptive quantitative analsysis with calculating the frequency, percentage, and mean score. The result of this research that EFL learners showed positive attitudes towards English phonetics learning based on indicators Direction, intensity, consistency, and spontaneity which categorized as good attitudes among the students proved their commitment to following instructional guidance as direction, demonstrating strong emotional engagement as intensity, maintaining steady dedication over the class learning as consistency and showing proactive initiative in their learning phonetic as spontaneity indicated that students' attitudes reflect a positive of good enthusiasm mastering English phonetics supported by effective teaching methods implemented at class.